Image Processing Application for Lipa Saqbe Mandar - Qashlim, Akhmad; Ochtavia, Gustia; Sarjan, Muhammad (Universitas Muhammadiyah Semarang Press, 2021)
Seeing from today's technological developments, it is growing rapidly, but there are still many people, especially the younger generation today, whose understanding is still very lacking, in recognizing any motifs or patterns in Lipa Saqbe Mandar. From these problems, an image processing application is needed to recognize the Lipa Saqbe pattern that can be used to help facilitate the community or the younger generation, where the camera application will be directed to Lipa Saqbe and will then provide information or identify the name of the Lipa Saqbe pattern or motif. This system uses the template matching method, which functions to match each part of an image with the image that becomes the template (reference). One of the applied methods of the convolution technique. This method is often used to identify character images of letters, numbers, fingerprints, and other image matching applications. This application is built using the Java programming language, and database. The image management process uses the template matching method through a scanning process so that it can identify the name of the motif or pattern in Lipa Saqbe